STUDI KOMPARASI KOMPETENSI PROFESIONAL GURU MATEMATIKA SMP NEGERI DI BALIKPAPAN DITINJAU BERDASARKAN GOLONGAN KEPANGKATAN - Husnul Khotimah (AlphaMath : Journal of Mathematics Education, 2016)
ABSTRACT The aim of this research is to find out the difference of professional competence mathematics teacher in SMP Negeri Balikpapan viewed from degree of official. This research is a comparison quantitative research where data were used from Dinas Pendidikan Balikpapan documents about teacher performance assessment in 2014. Degree of official in this research are third and fourth degree. The population were the entire mathematics teachers in SMP Negeri Balikpapan which were a hundred. Furthermore, 78 teachers were choosen as sample using random sampling technique. Analysis technique using t-test with 0,05 significance level. The result suggest that there is difference of professional competence of mathematics teacher of third and fouth degree (Sig = 0,012). Beside that, score professional competence mathematic teacher fourth degree is higher than third degree. KEYWORDS: professional competence, SMP mathematics teacher, degree of official